Dotação e talento: comparação das modalidades presencial e a distância de um programa de formação continuada para professores - Lopes, Jessica Fernanda [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Giftedness and talent correspond to a specifity of the Special Education that has aroused growing interest among academics, and the University plays the role of generating foreground information, as well as putting it at society's services. As this subject is rarely treated in the initial and continued teacher's education, it's established as objective of this research: to elaborate, apply and evaluate a continued educational program for teachers, performing it in dual mode (classroom and distance) and subsequently analyze and compared the results for each model, as well as to compare the perception of the teachers before and after the course. The program consisted of 52 hours with practical and theoretical activities, and has been applied in the virtual environment by a Distance Education Platform elaborated by the County Department of Education and the classroom group occurred weekly, at UNESP/Bauru campus. As programmatic content for this course it had been defined the following: a) Landmarks: Legal, historical and concept about Giftedness and Talent; b) Features of gifted and talent students; c) Identification and Specialized Educational Care; d) Schooling of gifted and talented students, and pedagogical practice; e) Creativity and the production of the Individualized Plan Teaching. Thirty-three teachers (divided in two groups) participated on this study, and the Conty Department of Education made their enrollment. Before the course's start, the participants answered two surveys, one to characterize the sample, and another to identify their conception about gifted and talented people, as well as about their concept about the course's content. Throughout the course at the end of each module, the teachers answered a review with closed questions on the content of the module. After the course, participants answered again the same instrument applied early in the course about their conceptionsof the gifted and talent population, as well...

Dotação e talento correspondem a uma especificidade da Educação Especial que vem despertando interesse crescente entre estudiosos e a Universidade tem o papel de produzir novos conhecimentos, bem como, de colocá-los a serviço da comunidade. Como raramente este tema é trabalhado na formação inicial e continuada de professores, delineou-se enquanto objetivo desta pesquisa: elaborar, aplicar e avaliar um programa de formação continuada para professores, realizando-o em duas modalidades de ensino (presencial e a distância) e, posteriormente, analisar e comparar os resultados obtidos nas duas modalidades, bem como a percepção dos professores antes e depois do curso. O Programa teve carga horária de 52 horas com atividades de cunho teórico-prático e foi aplicado, em ambiente virtual, por meio de uma plataforma de Educação à Distância (EaD) elaborada pela Secretaria Municipal de Educação, e os encontros da turma presencial aconteceram, semanalmente, no campus da Unesp/Bauru. Delimitou-se como conteúdo programático do curso: a) Marcos: legal, histórico e conceitual sobre Dotação e Talento; b) Caracterização dos alunos com Dotação e Talento; c) Identificação e Atendimento Educacional Especializado; d) Escolarização de alunos com Dotação e Talento e prática pedagógica; e) Criatividade e produção do Plano de Ensino Individualizado. Participaram do estudo 33 professores (divididos em duas turmas) cuja inscrição foi realizada na Secretaria Municipal de Educação. Antes do início do curso os participantes responderam a dois questionários, um, visando a caracterização da amostra, e outro para identificar as concepções deles sobre pessoas com Dotação e Talento, bem como, sobre o conteúdo do curso. Ao longo do curso ao final de cada módulo, os professores responderam uma avaliação com questões fechadas sobre o conteúdo do próprio módulo. Após o término do curso, os participantes responderam novamente...
Giftedness and talent: comparison between in-person and distance modality of a continued education program between in-person and distance modality of a continued education program for teachers
Keywords: Dotações; Aptidão; Professores - Formação; Educação permanente; Ensino a distância; Educação inclusiva; Endowments